2008
DOI: 10.1051/0004-6361:20078883
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the spectral energy distribution of ULIRGs

Abstract: Aims. By using the spectral energy distribution (SED) from the near-infrared to the radio of a statistically significant number of luminous infrared galaxies we determine important physical parameters for this population of objects. In particular we constrain the optical depth towards the luminosity source, the star formation rate, the star formation efficiency and the AGN fraction. Methods. We fit the near-infrared to radio spectral energy distributions of a sample of 30 luminous and ultra-luminous infrared g… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
131
5

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(152 citation statements)
references
References 150 publications
16
131
5
Order By: Relevance
“…Considering the observed 2-10 keV luminosity, the ratio is L L log 4.14 Using the relationship of Mullaney et al (2011) it is possible to convert the 2-10 keV luminosity into the expected IR ( ( ) ) = -we find that the IR luminosity of the AGN is between 0.1% and 0.6% of the total IR luminosity. This value is in disagreement with that obtained by Vega et al (2008) using spectral decomposition, who found that the contribution of the AGN to the total IR luminosity is about one order of magnitude larger. A 5% contribution to the total IR luminosity would imply that 9.6 Intrinsic 2-10 keV flux (F 2 10 -) (10 −12 erg s −1 cm −2 ) 2.6 intrinsic 10-50 keV flux (F 10 50 -)(10 −12 erg s −1 cm −2 ) 3.1 2-10 keV luminosity (L 2 10 -)(erg s −1 ) 2.01×10 42 10-50 keV luminosity (L 10 50 , also an order of magnitude larger than predicted by our X-ray spectral analysis.…”
Section: Agn Contribution To the Ir Luminositycontrasting
confidence: 99%
See 2 more Smart Citations
“…Considering the observed 2-10 keV luminosity, the ratio is L L log 4.14 Using the relationship of Mullaney et al (2011) it is possible to convert the 2-10 keV luminosity into the expected IR ( ( ) ) = -we find that the IR luminosity of the AGN is between 0.1% and 0.6% of the total IR luminosity. This value is in disagreement with that obtained by Vega et al (2008) using spectral decomposition, who found that the contribution of the AGN to the total IR luminosity is about one order of magnitude larger. A 5% contribution to the total IR luminosity would imply that 9.6 Intrinsic 2-10 keV flux (F 2 10 -) (10 −12 erg s −1 cm −2 ) 2.6 intrinsic 10-50 keV flux (F 10 50 -)(10 −12 erg s −1 cm −2 ) 3.1 2-10 keV luminosity (L 2 10 -)(erg s −1 ) 2.01×10 42 10-50 keV luminosity (L 10 50 , also an order of magnitude larger than predicted by our X-ray spectral analysis.…”
Section: Agn Contribution To the Ir Luminositycontrasting
confidence: 99%
“…It has been shown indeed that for AGNs the absorption-corrected 2-10 keV and the 6 and 12 μm luminosities are well-correlated (e.g., Gandhi et al 2009;Asmus et al 2015;Stern 2015) so that deviations from the correlation might imply the presence of heavy obscuration. Vega et al (2008) report that at 6 μm about 58% of the flux is produced by the AGN. This would imply that the ratio between the IR and observed X-ray AGN luminosity is very low: …”
Section: Ir and X-ray Tracers Of Agn Activity In U/lirgsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is not likely to be the case if the mechanism driving the FIR emission of AGN hosts was disparate from that of the SPIRE population with dormant nuclei (though see discussion in Hill & Shanks 2012 and references therein for a possible alternative viewpoint). Another line of evidence comes from a more complex treatment of local ULIRGS involving multi-component SED fitting by Vega et al (2008). In that study it was found that the bandpass spanning the rest-frame wavelengths 40 μm-500 μm was the least sensitive to the presence of a radio AGN, such that only ∼5% of their sample needed AGN contributions to the TIR luminosity in excess of 10% to properly reproduce the SEDs of their sample.…”
Section: Total Infrared Luminosities and Sfrsmentioning
confidence: 99%
“…Figure 2 presents the re-normalized average spectral energy distributions of each subsamples, together with the average infrared-optical spectra obtained for a sample of 30 ULIRGs (Vega et al 2008) for illustration. The spectra of the galaxy subsamples were re-normalized at 60 μm to the average obtained for the 30 ULIRGs.…”
Section: Average Spectral Energy Distributionmentioning
confidence: 99%